2021
DOI: 10.3389/fgene.2021.602429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Custom SNP Panel for Identifying and Rectifying of Misjudged Paternity in Deficiency Cases

Abstract: Parentage testing is routinely performed by genotyping short tandem repeat (STR) through capillary electrophoresis in the present. However, ambiguous or even misjudged paternity based on STRs happens from time to time in cases where only one putative parent is available. We analyzed STR data of 7,818,969 unrelated pairs and 75 close-relative pairs and found that although the probability of a random false match between non-relatives was 4.22 × 10–6, the incidence of false or ambiguous paternity results between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The gain or loss of tandem repeats could lead to false maternal or paternal exclusions [30,32]. In addition, erroneous results can be produced by false matches with close family members or even with people who are completely unrelated to the victim, such that, in some cases, a probability of paternity greater than 99.99% does not necessarily indicate biological paternity [30,31,[38][39][40][41]. Poetsch et al [31] investigated how many wrong paternity inclusions could be detected when comparing [13][14][15] STRs between 336 children and 348 unrelated men.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The gain or loss of tandem repeats could lead to false maternal or paternal exclusions [30,32]. In addition, erroneous results can be produced by false matches with close family members or even with people who are completely unrelated to the victim, such that, in some cases, a probability of paternity greater than 99.99% does not necessarily indicate biological paternity [30,31,[38][39][40][41]. Poetsch et al [31] investigated how many wrong paternity inclusions could be detected when comparing [13][14][15] STRs between 336 children and 348 unrelated men.…”
Section: Discussionmentioning
confidence: 99%
“…They found that at least one and up to three "second father(s)" could be found for 23 children. In general, the false inclusion rate ranges between 19% and 23% [40]. These problems are being reported more frequently and are most common in cases where only one putative parent is available [31,40,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MPS‐based iiSNP multiplexes lack extraneous artifacts such as stutter, which are routinely encountered when genotyping forensically relevant STRs on both MPS‐ and CE‐based platforms. Several iiSNP multiplexes have been developed with the primary goal of identity determination (Avent et al, 2019; Borsting et al, 2009; Chang et al, 2021; Churchill et al, 2016; Dixon et al, 2005; King et al, 2018; Pakstis et al, 2007; Sanchez et al, 2006; Vallone et al, 2005; Wei et al, 2014; Zhang et al, 2017).…”
Section: Snp Classesmentioning
confidence: 99%